Assistance Program for Facilitating the Enhancement of Educators’ Competence at BBPPMPV-BOE Malang - Fitriyani, Syefalia; Ajisaputra, Arnanda; Retnowati, Dewi; Shabri S, Moh. (Santoso Academy Network, 2025)
Internships serve as an essential form of contextual learning, enabling students to engage directly in professional activities and understand institutional work dynamics. This article aims to analyze the role and strategic contributions of internship students in supporting the facilitation program for enhancing educators' competence at BBPPMPV-BOE Malang. A qualitative approach was employed through participatory observation and narrative reflection, allowing students to be actively involved in administrative preparation, technical implementation, activity documentation, and report development throughout the training program. The findings indicate that students contributed significantly to improving coordination efficiency, strengthening documentation systems, and supporting the execution of workshops and upskilling programs for vocational teachers. Their involvement helped address human resource constraints, reduced operational workload, and provided reflective input for program evaluation. Additionally, the internship experience facilitated the development of students' professional competencies, particularly in communication, teamwork, and bureaucratic adaptation within a government training institution. The presence of interns was therefore not merely supplementary but strategically positioned to reinforce institutional capacity in delivering high-quality competence development for vocational teachers. This study highlights the importance of establishing structured internship partnerships between higher education institutions and vocational training centers to ensure sustained reciprocal benefits that develop both academic talent and institutional performance.